Bioprocess of Microbial Melanin Production and Isolation - Choi, Kwon Young (Frontiers in Bioengineering and Biotechnology, 2021)
Melanin is one of the most abundant pigments found in the biosphere. Owing to its high biocompatibility and diverse biological activities, it has been widely applied as a functional biomaterial in the cosmetic, pharmaceutical, biopolymer, and environmental fields. In this study, the production of melanin was comprehensively reviewed concerning bioconversion and isolation processes. First, several melanogenic microbes, including fungi and bacteria, were summarized. Melanin production was classified by host and melanin type and was analyzed by titers in g/L in addition to reaction conditions, including pH and temperature. The production was further interpreted using a space-time yields chart, which showed two distinct classifications in productivity, and reaction conditions were analyzed using a pH-temperature-titer chart. Next, the extraction process was summarized by crude and pure melanin preparation procedures, and the extraction yields were highlighted. Finally, the recent applications of melanin were briefly summarized, and prospects for further application and development in industrial applications were suggested.
Keywords: Bioconversion process; Bioprocesses; Classifieds; Environmental fields; Extraction process; Isolation process; Pharmaceutical fields; Preparation procedures; Reaction conditions; Space time yield; extraction; melanin; pigment; purification; space-time yields